Are Committees on Respect for International Law within universities a new threat to academic freedom? - Muraille, Eric (Frontiers in Education, 2026)
Following the escalation of the Israeli–Palestinian conflict after the Hamas attack of October 7, 2023, pro-Palestinian activists occupied universities in the United States, Canada, and Europe, demanding that academic authorities cut ties with Israeli institutions. This article examines the response of Belgian universities to these mobilizations. At first, several institutions rejected calls for an academic boycott and reaffirmed their commitment to institutional neutrality, emphasizing the importance of protecting academic freedom. Their actions were limited to reviewing whether collaborations with Israeli universities posed risks of harmful applications, particularly in the context of dual-use research. In contrast, the Ghent University and the Université Libre de Bruxelles quickly declared that a boycott was a necessity in light of Israel’s violations of international law and human rights. Both established Committees on Respect for International Law to reassess partnerships with foreign institutions. This stance soon became dominant within Belgian higher education. Through joint declarations, all Belgian universities endorsed an academic boycott and urged the European Union to suspend agreements with Israel. Such a position marks a clear departure from traditional academic norms. By abandoning institutional neutrality, universities positioned themselves as political actors, a shift that may reshape how both the public and policymakers perceive academic expertise, while also exposing institutions to political targeting. Moreover, by presenting the academic boycott as a moral and legal obligation, universities risk legitimizing the idea that scholarly communities can be held collectively responsible for state actions. If generalized across Europe, these practices could endanger academic freedom and normalize academic boycotts as a form of collective punishment.